Rational Number Operations: What (Mis)Understanding Do Children Demonstrate? - Graça, Sofia (2022)
This qualitative and interpretative study aims to know grade 5 children’s knowledge of rational number operations, before and after a teaching experiment emphasizing the use of models. Data was collected using two tests and four individual semi-structured interviews. The results show that, before the teaching experiment, in fraction addition and subtraction, children just applied rules. After the teaching experiment, they demonstrate conceptual understanding regarding these operations. In fraction multiplication and division, that involve a more complex conceptual understanding, they showed important ideas regarding rational number sense and operation sense. The use of models seems to have promoted the conceptual understanding of these operations by children.